2020
DOI: 10.1055/s-0040-1716527
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observational Study of Interfaced Smart-Pumps in Pediatric Intensive Care

Abstract: Background Processes for delivery of high-risk infusions in pediatric intensive care units (PICUs) are complex. Standard concentration infusions (SCIs), smart-pumps, and electronic prescribing are recommended medication error reduction strategies. Implementation rates in Europe lag behind those in the United States. Since 2012, the PICU of an Irish tertiary pediatric hospital has been using a smart-pump SCI library, interfaced with electronic infusion orders (Philips ICCA). The incidence of infusion errors is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The organisation-wide standardised provision of infusions in ready-toadminister presentations in a large children's hospital led to the almost complete elimination of medication administration errors [25][26][27]. A similar project in Ireland demonstrated the feasibility of implementing smart pumps and standard concentration infusions in paediatric services using a single national drug library, with evidence of effectiveness [11,28,29]. However, the implementation of these interventions has required ongoing sponsorship and coordination at a system level and cannot be led or managed at a local level.…”
Section: Areas Of Discussion At the Symposiummentioning
confidence: 99%
See 1 more Smart Citation
“…The organisation-wide standardised provision of infusions in ready-toadminister presentations in a large children's hospital led to the almost complete elimination of medication administration errors [25][26][27]. A similar project in Ireland demonstrated the feasibility of implementing smart pumps and standard concentration infusions in paediatric services using a single national drug library, with evidence of effectiveness [11,28,29]. However, the implementation of these interventions has required ongoing sponsorship and coordination at a system level and cannot be led or managed at a local level.…”
Section: Areas Of Discussion At the Symposiummentioning
confidence: 99%
“…While the data exploring the benefits of smart pump use are largely equivocal, this may be at least partly related to low uptake of smart pumps across healthcare systems, as well as poor drug library design [3,40,41]. However it is clear that smart pumps have a potential role in all areas where injectable medicines are used, to provide support for adoption and administration of standard infusions safely and consistently [29,36], to offer opportunities for system-wide learning, and to protect patients [9,36]. Smart pumps are most likely to prevent the most catastrophic events, with little impact on the day-to-day discrepancies and deviations seen in large, well-powered observational studies.…”
Section: Recommendation 2: Develop and Implement Drug Libraries Using...mentioning
confidence: 99%
“…We then verified whether the infusion pump settings could be matched with the injection order information. This was not a study of a "smart pump" [7][8][9][10][11] that automatically adjusts the drug speed and dosage; instead, we collected information from the infusion pump and used it for a injection order matching process. Although the linkage of data with smart pumps is innovative, it is not practical to obtain approval from the Japanese regulatory agency, the Pharmaceuticals and Medical Devices Agency.…”
Section: Objectivesmentioning
confidence: 99%
“…10,15,27,100 A new area of research interest was smart infusion pump interoperability with EHR, 62,69 also identified as an important area of development elsewhere. [8][9][10]29 Nonetheless, during the analysis process we observed that the current search strategy was not sensitive enough to detect all studies related to the EHR interoperability with smart infusion pump [102][103][104][105][106] and patient-controlled analgesia pumps. 107 Therefore, more targeted research objectives and search strategies are needed in future systematic reviews of new technologies to secure safe IV MMU process.…”
Section: Table 2 a Summary Of The Key Findings Of Studies Investigati...mentioning
confidence: 99%